Penyuluhan PHBS pada Anak Usia Dini di SDN 1 Baktiya untuk Membangun Kebiasaan Sehat Sejak Dini - Erna Safitri; Ananda Alfinura (Pusat Riset dan Inovasi Nasional, 2025)
Keude Pante Breuh, a village in Baktiya District, North Aceh Regency, shows great potential for development amidst the social, economic, and infrastructure challenges it faces. This study aims to identify the priorities, needs, and requirements of the village community in terms of education, health, economy, infrastructure, and social life. With an average income of 4–5 million rupiah per month and an unemployment rate of 30%, the village community prioritizes increasing job opportunities, improving infrastructure, and improving the quality of education and health. Although access to clean water, sanitation, and electricity is adequate, improving roads and public transportation remains an urgent need. This study provides a comprehensive picture of the village's condition and recommendations for further development. The research method used is a qualitative descriptive approach, with data collection through field observations, in-depth interviews with community leaders, and documentation studies. Observations were conducted to directly observe the physical condition of the village and the facilities available, while interviews were conducted to explore the community's views on their priorities and needs. Documentation studies were used to analyze secondary data, such as village reports and related government documents